Pengaruh Penyediaan Modul Keperawatan Halusinasi Terhadap Kemampuan Keluarga Dalam Merawat Anggota Keluarganya Yang Mengalami Halusinasi Tahun 2013 - Nilai Utami Nurhasanah; Ira Kusumawaty; Sari Wahyuni (POLITEKNIK KESEHATAN KEMENKES PALEMBANG, 2014)
Hallucinations can interfere perception of the five senses which include hallucinations of hear, see, smell, touch and taste, not only pose a nuisance to the patient concerned, however, resulted in doubled burden for the family. The diversity of behaviors that appear when clients back home for family raises its own stressors. Families are required to be able to care for family members who experienced hallucinations as a sub system so that clients can live independently family to live a life and not be a burden to the family . Hallucinations nursing module can be one of the tools to enhance the ability of families to care for family members who experience hallucinations. The purpose of this study was to determine the effect of the provision of nursing module hallucinations on the ability of families to care for family members who experience hallucinations. This research applied quantitative research methods,